2010
DOI: 10.1111/j.1528-1167.2010.02831.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenesis and epilepsy

Abstract: SUMMARYPersistent neural stem cells generate dentate granule cells (DGCs) throughout life. Evidence suggests that aberrant neurogenesis contributes to epileptic structural abnormalities, but that normally integrating adult-born DGCs may restore inhibition. Current research focuses on how epileptogenic insults alter neurogenesis, and whether restoring normal neurogenesis will attenuate epi- Persistent neural stem cells (NSCs) in the subgranular zone (SGZ) of the hippocampal dentate gyrus generate dentate granul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 4 publications
(6 reference statements)
1
11
0
Order By: Relevance
“…The mechanisms by which rapamycin produces these positive effects, however, are unclear. For the present study, we examined several hippocampal abnormalities implicated in the development of temporal lobe epilepsy (Parent and Kron, 2012; Hester and Danzer, 2014), including mossy fiber sprouting (Buckmaster, 2014), hilar ectopic granule cell accumulation (Scharfman and Pierce, 2012), basal dendrite formation (Ribak et al, 2012), reactive astrogliosis and microgliosis (Sharma et al, 2008; Gibbons et al, 2013) and mossy cell loss (Jinde et al, 2013). Consistent with previous studies (Zeng et al, 2009; Buckmaster et al, 2009), we observed a significant reduction in mossy fiber sprouting with rapamycin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which rapamycin produces these positive effects, however, are unclear. For the present study, we examined several hippocampal abnormalities implicated in the development of temporal lobe epilepsy (Parent and Kron, 2012; Hester and Danzer, 2014), including mossy fiber sprouting (Buckmaster, 2014), hilar ectopic granule cell accumulation (Scharfman and Pierce, 2012), basal dendrite formation (Ribak et al, 2012), reactive astrogliosis and microgliosis (Sharma et al, 2008; Gibbons et al, 2013) and mossy cell loss (Jinde et al, 2013). Consistent with previous studies (Zeng et al, 2009; Buckmaster et al, 2009), we observed a significant reduction in mossy fiber sprouting with rapamycin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While multiple causes have been proposed for SE-induced SRS, its link to hippocampal alterations such as the loss of different subclasses of GABA-ergic interneurons and failure of inhibition [69], persistent neuroinflammation typified by reactive astrocytes and activated microglia [75], and aberrant neurogenesis in the early phase after SE [19,76,77] have received significant support. On the other hand, SE-induced mood and memory dysfunction are likely linked to progressive loss of hippocampal principal neurons (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Next to its importance in spatial learning, the hippocampus is also the main target of action for stress hormones [30,53]. The effect of stressors combined with the damage caused by SE [34,54] leads to worse functioning of the hippocampus, which in turn amounts to impaired learning and memory formation. In contrast, low-stress settings, such as the hole board experiments performed here, support that the effects of stress are severe, as no impaired learning and memory were found in these settings [11][12][13] and lower corticosterone levels have been reported after completion of the task.…”
Section: Discussionmentioning
confidence: 99%
“…All behavioral tasks started 35 days after the induction of SE, with the exception of the elevated plus maze (EPM) task, which took place after the circular hole board (CHB) or modified hole board (MHB) task was completed (on days [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. In between trials, behavioral setups were cleaned with 0.1% acetic acid to eliminate odor cues.…”
Section: Behavioral Tasksmentioning
confidence: 99%